Design and implementation of a non-invasive real-time microwave sensor for assessing water hardness in heat exchangers - Teng, Kah Hou; Shaw, Andy; Ateeq, Muhammad; Al-Shamma'a, Ahmed; Wylie, Stephen; Kazi, Salim Newaz; Chew, Bee Teng; Kot, Patryk (Taylor & Francis, 2018)
A non-invasive-monitoring of concentration and dielectric properties of calcium hardness in heat exchanger cooling water was conducted with a 2.5 GHz microwave cavity resonator designed and fabricated locally for the experiment. The principle of electric dipole moment theories were used to analyse the sample solution that occurs as a function of calcium ion content. Artificial difference of water hardness was prepared by mixing CaCl2 in deionised water. The sample was centrally positioned in the electric field of the TM010 mode of a resonant cylindrical cavity. COMSOL simulation package was used to compare and validate the experimental cavity resonator frequency. Transmission signal (S21) measurements via vector network analyser at different concentrations were observed a linear relationship in amplitude with different frequency changes. In addition, calcium absorption provides a first-order change in material polarisation (i.e. real permittivity), and second-order transitions associated dielectric losses (i.e. imaginary permittivity). These research findings introduce a novel technique of real-time monitoring of water hardness concentration by using non-invasive microwave sensor.